Comparative transcriptome profile analysis of rice varieties with different tolerance to zinc deficiency - Lu, X.; Liu, S.; Zhi, S.; Chen, J.; Ye, G. (Wiley, 2021)
Zinc (Zn) is an indispensable element for rice growth. Zn deficiency results in brown blotches and streaks 2–3 weeks after transplanting, as well as stunting, reduced tillering, and low productivity of rice plants. These processes are controlled by different families of expressed genes. A comparative transcriptome profile analysis was conducted using the roots of two Zn deficiency tolerant varieties (UCP122 and KALIBORO26) and two sensitive varieties (IR26 and IR64) by merging data from untreated control (CK) and Zn deficiency treated samples. Results revealed a total of 4,688 differentially expressed genes (DEGs) between the normal Zn and deficient conditions, with 2,702 and 1,489 unique DEGs upregulated and downregulated, respectively. Functional enrichment analysis identified transcription factors (TFs), such as WRKY, MYB, ERF, and bHLH which are important in the regulation of the Zn deficiency response. Furthermore, chitinases, jasmonic acid, and phenylpropanoid pathways were found to be important in the Zn deficiency response. The metal tolerance protein (MTP) genes also appeared to play an important role in conferring tolerance to Zn deficiency. A heavy metal‐associated domain‐containing protein 7 was associated with tolerance to Zn deficiency and negatively regulated downstream genes. Collectively, our findings provide valuable expression patterns and candidate genes for the study of molecular mechanisms underlying the response to Zn deficiency and for improvements in breeding for tolerance to Zn deficiency in rice.Zinc (Zn) is an indispensable element for rice growth. Zn deficiency results in brown blotches and streaks 2–3 weeks after transplanting, as well as stunting, reduced tillering, and low productivity of rice plants. These processes are controlled by different families of expressed genes.A comparative transcriptome profile analysis was conducted using the roots of two Zn deficiency tolerant varieties (UCP122 and KALIBORO26) and two sensitive varieties (IR26 and IR64) by merging data from untreated control (CK) and Zn deficiency treated samples.Results revealed a total of 4,688 differentially expressed genes (DEGs) between the normal Zn and deficient conditions, with 2,702 and 1,489 unique DEGs upregulated and downregulated, respectively. Functional enrichment analysis identified transcription factors (TFs), such as WRKY, MYB, ERF, and bHLH which are important in the regulation of the Zn deficiency response. Furthermore, chitinases, jasmonic acid, and phenylpropanoid pathways were found to be important in the Zn deficiency response. The metal tolerance protein (MTP) genes also appeared to play an important role in conferring tolerance to Zn deficiency. A heavy metal‐associated domain‐containing protein 7 was associated with tolerance to Zn deficiency and negatively regulated downstream genes.Collectively, our findings provide valuable expression patterns and candidate genes for the study of molecular mechanisms underlying the response to Zn deficiency and for improvements in breeding for tolerance to Zn deficiency in rice.